2010
DOI: 10.1063/1.3340939
|View full text |Cite
|
Sign up to set email alerts
|

Stable temperature characteristics of InGaN blue light emitting diodes using AlGaN/GaN/InGaN superlattices as electron blocking layer

Abstract: Articles you may be interested inInvestigations on correlation between I-V characteristic and internal quantum efficiency of blue (AlGaIn)N light-emitting diodes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…However, improvement via conventional EBLs is limited due to the severe band bending of the EBL caused by strong electrostatic fields and low effective energy height [18]. Studies have also shown that inserting a superlattice EBL layer is conducive to the blue LEDs of InGaN materials [19][20][21], but there have been fewer studies on the superlattice EBL of deep UV LEDs. This study investigates different Al mole compositions of conventional EBL as they affect the performance of the optical device, then replaces the conventional EBL with a superlattice EBL, Simulation results show the performance of the deep UV LED with superlattice EBL improves tremendously.…”
Section: Introductionmentioning
confidence: 97%
“…However, improvement via conventional EBLs is limited due to the severe band bending of the EBL caused by strong electrostatic fields and low effective energy height [18]. Studies have also shown that inserting a superlattice EBL layer is conducive to the blue LEDs of InGaN materials [19][20][21], but there have been fewer studies on the superlattice EBL of deep UV LEDs. This study investigates different Al mole compositions of conventional EBL as they affect the performance of the optical device, then replaces the conventional EBL with a superlattice EBL, Simulation results show the performance of the deep UV LED with superlattice EBL improves tremendously.…”
Section: Introductionmentioning
confidence: 97%
“…An increased Al content in the EBL for a stronger electron confinement simultaneously makes it more difficult for holes to enter the MQWs. Thus, several InGaN/GaN LEDs with novel p-EBL designs have been proposed [10][11][12] to mitigate the problem. Moreover, an n-type doped EBL structure, 13 an InGaN staircase electron injector, 14 and polarization matched AlGaInN quantum barriers (QBs) 6 have also been proposed to suppress the electron leakage.…”
mentioning
confidence: 99%
“…However, the structure and parameters of the quantum well (QW) and the quantum barrier are highly dependent on the polarization fields (piezoelectric and spontaneous fields) and cannot be ignored. [28][29][30] In this study, the optical and electrical characteristics of InGaN/GaN blue LEDs with the same composition but different well thicknesses at various ambient temperatures will be discussed. [12][13][14] Recently, some researchers have designed some structures of staggered QWs, [15][16][17] InGaN-delta-AlGaN or InN QWs, 18,19 strain-compensated QWs, 20,21 and graded-composition barriers, 22 to improve the optical properties of nitridebased LEDs.…”
Section: Introductionmentioning
confidence: 99%